Bibliometric analysis of public health research in Africa: The overall trend and regional comparisons - Kun-Yang Chuang; Ying-Chih Chuang; Meng Ho; Yuh-Shan Ho (South African Journal of Science)
Many diseases in Africa can be prevented with appropriate public health interventions. This study aimed to assess the bibliometric characteristics of public health related research articles published by researchers in African institutions from 1991 to 2005. Data used in this study were obtained from the online version of the ISI Web of Science: Science Citation Index Expanded (SCI-Expanded). Articles published between 1991 and 2005 that had the phrase 'public health' in the title, author keywords or abstract, and had at least one author whose contact address was in an African country, were selected for analysis. The annual number of public health related articles published by African researchers significantly increased from 28 articles in 1991 to 135 articles in 2005, a 382% increase. International collaboration also increased: from 45% of articles having international collaborators during 1991-1995, to 52% during1996-2000, and to 67% during 2001-2005. Collaborations were mostly with European and North American countries. Keywords, subject categories and collaboration patterns of articles varied across regions, reflecting differences in needs and collaboration networks. Public health related research output, as well as international collaborations, have been increasing in Africa. Regional variation observed in this study may assist policymakers to facilitate the advancement of public health research in different regions of Africa, and could be useful for international organisations in identifying needs and to allocate research funding. Future bibliometric analyses of articles published by African researchers, can consider conducting regional comparisons using standardised methods, as well as describing the overall patterns, in order to provide a more comprehensive view of their bibliometric characteristics.